HUBUNGAN ANTARA FAKTOR-FAKTOR INTERNAL DENGAN EVALUASI HASIL BELAJAR MAHASISWA DI AKPER PAMENANG PARE KEDIRI - Cahyono, Aris Dwi (Jurnal AKP, 2010)
Evaluation result of learning to emphazise to obtainingof information about how acquirement of student inreachingÂ  onÂ  targetÂ  ofÂ  specifiedÂ  instruction.Â  EvaluationÂ  resultÂ  ofÂ  learningÂ  canÂ  influenceÂ  byÂ  someÂ  factorÂ  amongothers motivator factor learn, habit learn and effeciency attend the lecture.TargetÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  studyÂ  internalÂ  factorsÂ  relatedÂ  toÂ  evaluationÂ  resultÂ  ofÂ  learningÂ  inÂ  AkperPamenang Pare.The research design which used was the cross sectional. The samples taken away from all student mount IItotallyÂ  samplingÂ  numberÂ  ofÂ  48Â  student.Â  Instrument usedÂ  forÂ  dataÂ  collectingÂ  documentationÂ  andÂ  questtionnaireresultÂ  ofÂ  evaluationÂ  learn evenÂ  semesterÂ  student (semesterÂ  II)Â  periodeÂ  ofÂ  yearÂ  2004/2005.Â  DataÂ  processingÂ  usestatistical test (SPSS) Spearman RhoâS with level of significanceÎ± < 0,05.Result of data processing with SPSS Spearman RhoâS show there are relation between motivation learn withevaluationÂ  resultÂ  ofÂ  learningÂ  (Î±Â  =Â  0,038),Â  thereÂ  areÂ  relationÂ  betweenÂ  habitÂ  learnÂ  withÂ  resultÂ  ofÂ  learningÂ  (Î±Â  =0,013) and do not there are relation between sufficiency attend the lecture with evaluation result of learning (Î±= 0,455).Conclusion of this research there are relation between motivation factor learn, habit learn and efficiency attendthe lecture with evaluation result of learning student Akper Pamenang Pare. So that motivate to learn, habitlearn and efficiency attend the lecture student require to be improved to beÂ  more improve achievement learn, byperforming atuition to studentKeywords: Evaluate result learn, motivation learn,habit learn, efficiency attend the lecture..